Challenges and Countermeasures of Targeted Scientific and Technical Novelty Search - XIA Dong, XU Yingqi, WANG Chao, REN Bo (Nongye tushu qingbao xuebao, 2022)
[Purpose/Significance] In order to meet the scientific and technological information needs of different subjects and improve the quality of scientific and technological novelty search, the challenges to the targeted scientific and technological novelty search are analyzed and corresponding countermeasures are put forward. [Method/Process] We introduce the connotation of targeted scientific and technological novelty search, sort out the methods of the novelty search, and analyze the challenges and put forward countermeasures. [Results/Conclusions] The challenges to the targeted scientific and technological novelty search include the precise search for the in-depth novelty content, the wide intersection of subject knowledge, the novelty search process focused on value and data, prevention of omission of literature retrieval in other languages, and consideration on both quality and efficiency. The targeted scientific and technological novelty search needs to build targeted literature resources, develop team cooperation services, strengthen the job competence of novelty searchers, and formulate guidelines and evaluation standards.